2018
DOI: 10.1080/21505594.2018.1537730
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa LptE is crucial for LptD assembly, cell envelope integrity, antibiotic resistance and virulence

Abstract: Lipopolysaccharide (LPS) is an essential structural component of the outer membrane (OM) of most Gram-negative bacteria. In the model organism Escherichia coli, LPS transport to the OM requires seven essential proteins (LptABCDEFG) that form a continuous bridge across the cell envelope. In Pseudomonas aeruginosa the recently-demonstrated essentiality of LptD and LptH, the P. aeruginosa LptA homologue, confirmed the crucial role of the Lpt system and, thus, of LPS in OM biogenesis in this species. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 72 publications
6
34
0
Order By: Relevance
“…Downregulation of LptE did lead to a defect in membrane permeability, which is consistent with our observations here for the defect in Z61 LptE. The membrane defect resulting from LptE downregulation appeared to result at least in part from depletion of the LptD protein, which forms a complex with LptE, reflecting a compromised chaperone function of LptE in the formation of this active LptE-LptD complex rather than a direct role for LptE in LPS transport (47). This was proposed to lead to drug sensitivity based on the indirect effect of reduced LptD levels on LPS transport and cell division, as well as the possibility that nonstabilized LptD transporter barrel proteins lacking inserted LptE may circumvent the OM permeability barrier (47).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Downregulation of LptE did lead to a defect in membrane permeability, which is consistent with our observations here for the defect in Z61 LptE. The membrane defect resulting from LptE downregulation appeared to result at least in part from depletion of the LptD protein, which forms a complex with LptE, reflecting a compromised chaperone function of LptE in the formation of this active LptE-LptD complex rather than a direct role for LptE in LPS transport (47). This was proposed to lead to drug sensitivity based on the indirect effect of reduced LptD levels on LPS transport and cell division, as well as the possibility that nonstabilized LptD transporter barrel proteins lacking inserted LptE may circumvent the OM permeability barrier (47).…”
Section: Discussionsupporting
confidence: 88%
“…The LptD protein component of the LptE-LptD translocon that mediates the final steps of LPS transport (7) is essential for growth in P. aeruginosa, as clearly demonstrated genetically and via specific chemical inhibition (44)(45)(46). It has recently been questioned whether LptE is also essential in P. aeruginosa (47) as it is in E. coli (48). Early studies using saturation transposon mutagenesis suggested an inability to inactivate lptE in P. aeruginosa PAO1 or PA14 (49,50), whereas more recent experiments using transposon sequencing indicated the existence of insertions in lptE (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein, together with LptD, is involved in the assembly of lipopolysaccharide (LPS) at the surface of the outer membrane. Alterations in lipopolysaccharide have been previously linked to virulence (Lo Sciuto et al, ). Results indicated clear alterations on LPS of Y. ruckeri 150 CTX.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, and opposite what happens in Salmonella Typhimurium, this change in metabolism resulted in a total attenuation of virulence in Y. ruckeri.The second protein upregulated in Y. ruckeri CTX 150 was LptE. This protein, together with LptD, is involved in the assembly of lipopolysaccharide (LPS) at the surface of the outer membrane.Alterations in lipopolysaccharide have been previously linked to virulence(Lo Sciuto et al, 2018). Results indicated clear alterations on LPS of Y. ruckeri 150 CTX.…”
mentioning
confidence: 87%